Linear viscoelastic of non-crimp fabric - Mohammad Hasbullah, Haris (Universiti Malaysia Sarawak, (UNIMAS), 2004)
This project focuses on the linear viscoelastic behaviour of Non-Crimp Fabrics. There are two types of fabric that have been used in this project which are chain stitch and tricot stitch non-crimp fabric. Both fabrics were clamped on picture frame and mounted to the testometric machine. The speed that has been used is 10 mm/min and there are two different loadings; which are perpendicular and parallel to the fabric stitch. In this experiment, it clearly shows that shear deformation curve comprises of two regions which are linear and non-linear. From the linear region, the experiment was continued with the stress relaxation test where the graph shows loads against times. This was done by using the selected loads (within the linear region). The test is continued until the desired load is achieved and the time is recorded. Then the results were used to develop the shear stress graph by using the mathematical equations and in order to find the viscoelastic bahaviours of the fabrics, the information from the graph was used to find the parameters which would determine the viscoelastic properties of the fabrics. From the experiment, it shows that chain stitch perpendicular to the loading and tricot stitch parallel to loading are more elastic compared to other loading direction for both fabrics. While compared to the other directions of the fabrics, it is clear that tricot stitch fabric with stitch perpendicular to loading is more elastic due to the tight stitch than the chain stitch fabric with stitch parallel to loading, where it shows the viscous behaviour.